PENINGKATAN DAYA KECAMBAH BENIH MAKADAMIA (Macadamia integrifolia) PADA BERBAGAI KONDISI MELALUI SKARIFIKASI - Ulfah, Inaya; Wardah, Wardah; Wahyuni, Dewi; Muslimin, Muslimin (Universitas Tadulako, 2020)
Macadamia (Macadamia integrifolia) is one kind of tree that have highly prospects as a non forest timber product. Macadamia produce nut that has many benefits. Macadamia nut were widely used in the food industry such as cookies, ice cream, candy and chocolate blend. One of the obstacles to Macadamia were to the processing a quality seeds for the cultivication of plants has not unfulfilled, so it must be imported from Australia. That’s why we need to research how to establish Macadamia plantation in improving germination process by using environmentally friendly technology to save the time, energy, and materials. The purpose of this research was to know the effect of seed condition and scarification. The method used was a complete randomized design, with two factors to impacted seeds. First one is seeds condition that are unintact (K1),intact (K2), and cracked (K3). Second one is scarification with the handling S0 (without submersion), S1(submersion with cool water for 24 hours), and S2 (submersion for 24 hours and drying for 3 hours). The result showed that the condition of seeds and scarification significantly effect gemination rate percentage (%), and germination seeds (day), but no significantly effect on height seedling (cm) in Macadamia. The best interaction of condition and scarification obtained intact the seeds that submersed by cool water for 24 hours and drying for 3 hours.Keywords: Macadamia integrifolia, Seeds, Scarification, Submersion.